The meaning of turtle symbols in the lyrics of the song Geobugi by Davichi - Syifa Muthia Hanifah; Putu Pramania Adnyana (Journal of Korean Applied Linguistics, 2022)
Song lyrics are literary works that comprise linguistic symbols that possess meaning. This study examines the meaning of the turtle symbol used in the lyrics of a Korean song by Davichi named Geobugi. The purpose of this study is to describe the meaning of turtle in the lyrics of the song Geobugi by Davichi. This study uses a qualitative descriptive method to systematically describe the meaning of denotation, connotation, and myth using the theory of semiotics by Roland Barthes. The research results showed that the turtle in the lyrics of the song Geobugi symbolizes cautiousness, patience, self-reflection, hope, and self-defense. The turtle symbol depicted in the lyrics of this song conveys the message that humans can move slowly and patiently, do self-reflection, remain optimistic in difficult times, and have their defense mechanisms. The discovery of the meaning of myth provides a new perspective that something contradictory can be perceived as an option rather than a negative thing, which differs from the general perception of the dynamic and fast-moving Korean society.